Yields of e0-electrons from the target surface by bombarding it by α-particles of different energies in the range from 0.9 to 5.5 MeV - V. T. Kupryashkin; L. P. Sidorenko; A. I. Feoktistov; V. A. Lasko (Ядерна фізика та енергетика)
The yields near-zero energy electrons(e0-electrons) and fast electrons (ef-electrons) in the bombardment of targets of aluminum and titanium by α-particles of 238Pu in the low-energy α-particles region (range 0.9 - 5.5 MeV) were measured. An increase in output e0- and ef-electrons is observed when the energy of α-particles is reduced. Outputs e0-electrons for α-particles of different energies Eα in this area is well described by the depend-ence (E)  E-1/2  v-1 as previously has been observed in our studies of the decay of 226Ra (range 4.7 - 7.6 MeV) and the bombardment of the target by α-particles at cyclotron U-120 (range 9.7 - 24 3 MeV).